Types and causes of students’ disruptive behavior in classroom at comprehensive level in Khyber Pakhtunkhwa, Pakistan - Turi, Jamshid Ali (Universiti Malaysia Pahang, 2019)
Disruptive behaviors have been ranked as the most triggering obstacle in the effective teaching-learning processes in the classroom environment. Moreover, it has been also reported that students in the govt: owned school feels more insecure as compared to the private school system. Among many, one is the inability of the teacher to manage and control the class in best possible way. In this study 400 teachers were taken as a sample. Questionnaire was adopted to evaluate the responses on 5-point Likert Scale ranging from 1= strongly disagree to 5= Strongly agree. Most of the disrupted behaviors were reported unanimously by the teacher. The study recommends that an extensive policy may be devised by the educators and proper training of the teacher may be given to the teacher for the social and emotional development of the student.